PENGURUSAN PEROLEHAN KOLEKSI DI MUZIUM KUCING, SARAWAK - MUHAMMAD ZAIDI, ABANG (Perpustakaan Tun Abdul Rahman Ya’kub (PeTARY), 2018)
This study is about managing Collecrion Acquisition at the Cat Museum, Sarawak. The problem in this sludy is rhe decreasing collection rOle every year has effect the visitor's arrival to the museum. This study is based on Ihree objectives. The firsl objeclive is to identify the collection resources at Ihe Cal Museum. The second objeclive is 10 invesligate Ihe faclors of lack the collections in Ihe museum. Proposing Ihe initialives that cal1 be pracliced by the Cal Museum 10 raise colieclion roles is Ihe lasl objective. The researcher used qualitalive melhod in order 10 gel Ihe dala for Ihis study.